POLONEZII ÎN CULTURA REPUBLICII MOLDOVA - NEDZELSCHI, şef oficiu, Filiala „A. Mickiewicz”, Ecaterina (BIBLIOPOLIS, 2020)
The Poles have arrived in the Bessarabia after the defeat of many insurrections in the years against the occupants – 1794, 1830, 1863. The insurrections wehe suppressed and the Poles roamed in search of refuge. Those that came in Bessarabia formed several polish settlements. A long time they were under special police surveillance. The historical situation and the linguistic policy of the communists deprived Poles to speak their language. The great personalities of Polish origin settled in Moldova had a significant role in the cultural life of the region. Inteligent, skilled, talented they occupied a special place in the Moldavian culture and imparted knowledge to the young generation. Among them: Pavel Şillingovski, Constantin Lodzieski, Vanda Zadnipru, Lidia Lipkovschi, Ludmila Nedremskaia, Galina Furdui, Nina Crulicovschi, Victoria Selitscaia, Victor Szimanowski.